C. elegans odour detection in the diagnosis of prostate cancer - Rinta-Kanto, Laura (My University, 2023)
There are about 200 distinct forms of cancer, each of which is diagnosed and treated differently. Early identification and treatment of cancer is especially important as the population ages and cases become more frequent. In Finland prostate cancer is the most prevalent cancer in men with approximately 5000 new cases and 900 deaths yearly. There are nearly 1,3 million cases globally every year. Despite advances in recent years, prostate cancer continues to be a significant medical issue for afflicted men, with overtreatment of benign illness and lack of effective medicines for metastatic prostate cancer. Prostate cancer rarely displays symptoms until it is incurable. Present technologies are unable to reliably identify between those tumours that will advance so slowly that they will not generate symptoms and those that are likely to cause death. As there is no sure way to prevent prostate cancer, the only way to reduce suffering and mortality is via early identification and competent patient care. Early detection followed by appropriate treatment plays a big role in the recovery while economical and accessible diagnosis methods are of vital importance. Presently prostate-specific antigen (PSA) screening is frequently employed for detecting prostate cancer in its early state. However, it is considered a controversial method, since around 67% of men with an elevated PSA level obtain a false positive result and are not diagnosed with prostate cancer, whereas 15% of men with a negative result will develop cancer. The Caenorhabditis elegans nematodes are widely used in research as a model organism since they are easy to maintain and possess many well-defined features. These include an efficient chemosensory system, which allows C. elegans to distinguish between substances in its surroundings and move towards or away from them. The chemosensory neurons in the head of C. elegans express around 700 distinct G protein–coupled receptors (GPCRs) that are able to recognize soluble or volatile compounds (VOCs) from the urine and exhaled air of cancer patients. It is thought that cancer metabolism generates particular odorants that could be useful in the early detection of the disease. The goal of this study was to determine how well the C. elegans nematodes can detect prostate cancer from human urine samples. Chemotaxis assays were performed with urine samples of men with either benign hyperplasia of the prostate or malignant prostate cancer. Results obtained during this study were fairly variable and not reliable enough to recommend the method for clinical use. However, several factors may have influenced the results that were not in line with previously published data. Thus, further studies on this topic are definitely needed.
Keywords: Cancer, prostate cancer, C. elegans, nematode, olfaction, chemotaxis, diagnostics